STRATEGIC DIGITAL CITY: A Survey in the Southeastern Brazil Capital Cities - Rezende, Denis Alcides; Teixeira, Alex Volnei; Cavichiolo Flores, Carla; From, Danieli Aparecida; Aguilar Lopes, Luisa (Perspectivas Contemporâneas, 2019)
Cities and their citizens connect through information and public services, and municipal strategies and information technology resources can strengthen urban social relations. The objective is to analyze city strategies, city information, transactional public services, information technology resources, and their relationship with strategic digital city projects. The research methodology included a survey with citizens of the four Southeastern Brazil capital cities: Belo Horizonte, Rio de Janeiro, São Paulo, and Vitória. Results revealed 718 non-formal components of a strategic digital city with variations that reflect the identities of each city. The research points out that the four cities have city strategies, city information, public services, and IT-based resources meeting the requirements to be regarded as strategic digital cities. The conclusion reiterates the relevance of city strategies and democratization of the use of city information.